The Purpose and Functions of Evaluation of Arabic Learning in Educational Administration Review - Iis Susiawati; Raswan Raswan; Dadan Mardani (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
This article approach uses qualitative methods with descriptive data collection techniques from literature studies. The data analysis technique uses the Seidel model by going through several stages of the process, namely identifying the collected data by means of data clarification, licensing, analysis, and data categorization. The discussion includes the meaning and differences between measurement, assessment, evaluation as well as the purpose and function of evaluation in Arabic language learning based on a review of educational administration. The three terms have different meanings but are interrelated with each other. The activity of comparing certain criteria to the results of observations is called measurement. Self-assessment means the process of collecting data by measuring, interpreting, describing, and interpreting some evidence of information from the measurement results. Meanwhile, evaluation is an advanced process of measurement and assessment data. The evaluation objectives to be achieved are determined by the evaluation function itself, which is divided into an instructional evaluation function, an administrative evaluation function, and a guidance evaluation function. The purpose and function of evaluation in the learning process go hand in hand, namely to obtain accurate information or data related to the level of achievement of student competencies in accordance with the instructional objectives or indicators formulated.